Factors affecting the diet of Peregrine Falcon in Italy (Avocetta, 2016)
The diet of top predators can provide useful information on phenology and abundance of their prey. The cosmopolitan and specialist Peregrine Falcon Falco peregrinus is an ideal model to assess whether food changes have occurred in the long-term. In this contribution, we reviewed all available literature on Peregrine Falcon diet in Italy which contained 11 detailed datasets useful for our review, and also included analysis of pellets, collected at three breeding sites of Sicily during 2014 and 2015. These data allowed us to shed light on the Peregrine Falcon’s diet over the last forty years (1978-2015). We calculated the numerical and biomass percentage of the resident and not-resident prey proportions, as well as the trophic diversity of diet in each site using the Simpson diversity index. To describe the Peregrine Falcon food niche and investigate whether year, habitat and latitude effects existed in its diet, we used a 2nd-degree factorial ANOVA. Over 1,550 prey, 110 bird species accounted for 98.58% of frequency and 99.79% of biomass. Modelling showed a year effect, with the quota and biomass of resident prey species increasing across the forty years of the study period, in a way complementary to the decrease of the quota and biomass of not-resident prey species. Conversely, habitat and latitude predicted significantly trophic diversity that was larger in rural than urban habitats, and at northern than southern latitudes. The strong numerical and biomass decrease of not-resident prey in the trophic niche of Peregrine Falcon in Italy could be related to the negative population trends of both migratory and summer-breeder farmland species. Actually the bulk of prey of the Peregrine Falcon in Italy is formed by a restricted group of resident Corvidae and Columbidae, which have remarkably increased in the last years. This could trigger more dependence on resident prey in the long term, making the Peregrine Falcons more vulnerable to control programs or eradication of specific prey populations or exposing them locally to high risk of infections (chlamydiosis, avian trichomiasis) transferred by feral species.